0.5ZnO@Cu5.4O nanoparticle for regulates the expression of GSDMB and targeted therapy of tumor - Hao Zhang; Guoyan Liu (Cancer Cell International)
Abstract GSDMB, a key protein in pyroptosis, is closely linked to various diseases. Nanomaterials can target and regulate specific pathways. Herein, we report a simple and efficient one-step method to develop multi-enzyme nanoparticles capable of suppressing GSDMB expression. 0.5ZnO@Cu5.4O can inhibit GSDMB, a capability that neither ZnO nor Cu5.4O possesses. ZnO@Cu5.4O with different ratios also exhibits varying inhibitory effects. The 0.5ZnO@Cu5.4O can be cleared quickly in vivo, ensuring biocompatibility. Additionally, 0.5ZnO@Cu5.4O significantly inhibits tumor progression, offering promising avenues for clinical cancer therapy, and the development of gene-regulating nanoparticles.